Integrated Strategy for Enhancing Sheep Flock Productivity - Tebourbi, Ons; Rekik, Mourad; Haile, Aynalem; Getachew, Tesfaye (International Center for Agricultural Research in the Dry Areas, 2024)
The optimization of sheep flock performances has always been a great challenge in improving productivity and the quality of production, in purpose of responding to markets’ demands and consumers’ specific preferences. In many developing countries, this challenge is even more difficult given their economic, social, cultural and educational current conditions. For this reason, enhancing the productivity of small ruminant flocks requires integrated, practical, low-cost and easy-to-implement solutions. Recognizing these challenges in many developing countries like Ethiopia, Mali, Jordan, etc., the International Center for Agricultural Research in the Dry Areas (ICARDA) has tested many solutions that have proven effective in improving sheep productivity. These include optimizing flock composition through selection, detecting early pregnancy using ultrasonography, and breeding soundness examinations to select the best sires for reproduction. This manual provides simple, tested and practical guidelines for the different actors involved in livestock development in Sudan, covering animal selection, ultrasound pregnancy diagnosis and sire assessment for reproduction.